Efficiency of hyaluronic acid versus red injectable platelet-rich fibrin (I-PRF) in treatment of stage III periodontitis: Randomized controlled clinical trial - Toleen MAZLOUM; Ghassan S. AMHAZ; Ghanem H. ABDULLAH; Nayer ABOELSAAD (International Arab Journal of Dentistry (IAJD), 2023)
Introduction: This study aims to compare clinical efficacy of red injectable platelet-rich fibrin (i-PRF) and hyaluronic acid (HA) as adjuncts to professional mechanical plaque removal (PMPR) in non-surgical management of stage III periodontitis.Methods: 75 patients were split into groups: group one (G1) received HA, group two (G2) received red i-PRF, and group three (G3), received only PMPR. Periodontal evaluation was done at baseline, 4th, 8th, and 12th weeks following treatment.Results: The plaque index, gingival index, and bleeding on probing were significantly improved in all groups. Moreover, the probing depth in all three groups displayed lower levels over the three months, with G1 and G2 experiencing the greatest declines. Additionally, G1 and G2 showed a considerable increase in clinical attachment level, while G3 showed no improvement.Conclusions: Thus, the application of HA and red i-PRF in conjunction with PMPR significantly improves all periodontal metrics, however, there is no statistically significant distinction between them.